ENVIRONMENTAL SUSTAINABILITY IN TOURISM: PERSPECTIVES FOR UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the role of environmental sustainability in tourism with a focus on Uzbekistan. A comparative-analytical approach was applied, including bibliometric review, case study analysis, SWOT assessment, and statistical data from UNWTO, WTTC, Statista, and Goskomstat. International practices from Spain, Singapore, the UAE, and South Korea demonstrate clear benefits of green tourism: lower operational costs, wider eco-certification, and stronger destination competitiveness. In Uzbekistan, fewer than 10% of facilities currently apply sustainable standards, but initiatives such as Priaralye National Nature Park and eco-trails in Chimgan indicate growing potential. The study argues that national eco-certification, renewable energy adoption, and community participation could accelerate progress. If effectively implemented, these measures would enhance international competitiveness, support biodiversity conservation, and position Uzbekistan as an emerging green tourism hub in Central Asia.
Keywords: Green tourism, sustainable tourism, environmental sustainability, Uzbekistan, ecotourism, eco-certification, renewable energy, SWOT analysis, Central Asia.